Human Africa Trypanosomiasis in Littoral Region of Cameroon: an Updated With First Evidence on the Circulation of Trypanosoma Brucei Gambiense in Manoka Island (International Journal of Scientific Research and Management (IJSRM), 2022)
Aims: A survey on Human African Trypanosomiasis (HAT) is essential for prevention and preparedness for epidemics. The objective of this study is to assess the circulation of human trypanosomes and their vectors across quiescent HAT foci of the Littoral Region of Cameroon. Methodology: A descriptive study on the presence of Trypanosoma brucei gambiense and its potential vectors was carried out in Youpwe, Yabassi, Sodiko, Manoka island and Cape-Cameroon Island from February to April 2022.Tsetse flies collected from the five selected locations using pyramidal traps, were first classified by species according to their morphology, then by sub-species with Polymerase Chain Reaction Diagnostic (PCR-Diag). Trypanosoma species and sub-species were subsequently identified and genotyped using a Nested PCR. Results: Glossina palpalis palpalis was the unique tsetse subspecies recorded across the five locations. The tsetse infection rate by Trypanosoma ssp. varied between 5.35% in Cape-island and 35.71% in Manoka island. Three Trypanosoma species were detected: T. brucei s.l. 32/500 (6.4%), T. congolense 15/500 (3.0%), and T. vivax 8/500 (1.6%). The sub-species T. b. gambiense responsible for HAT was detected in tsetse flies from Manoka (2/150: 1.33%), whereas T. congolense consisted of T. congolense “forest” and T. congolense “savannah” types. Conclusion: The presence of T. b. gambiense and T. congolense sub-species in Manoka and nearby suggests residual circulation of human and animal trypanosomes in quiescent HAT foci of the littoral region of Cameroon.